Copy protection system for digital home networks. - Andreaux, J.-P.
This article describes the rationale supporting and design of a copy protection system called SmartRight. While carefully presenting our motivations, some light is shed on the very peculiar problems raised by the enforcement of copy protection. Hence, this article also explores less technical but highly important issues such as the legal and commercial aspects.
Keywords: SmartRight; Content management; Copy protection system; Digital home networks; Digital rights management; Legal aspects; Personal private network; Renewability; Socioeconomic aspects